PELATIHAN PENGENALAN BANTUAN HIDUP DASAR PADA KOMUNITAS GOWES BIKELAH - Wiwiek Poedjiastoeti; Aryadi Subrata; Indrajadi Gunardi; Albert (JURNAL ABDIMAS KESEHATAN TERPADU, 2022)
Today, cardiovascular disease is the second biggest cause of mortality worldwide, after cancer. In urban communities, bicycle communities are also activated by an awareness of the significance of staying fit through exercise, particularly cycling. Nonetheless, sports can also trigger health issues, such as heart attacks or cardiac arrest due to fatigue or exhaustion. Numerous common individuals are unfamiliar with the terms basic life support and cardiopulmonary resuscitation, and hence lack the confidence to assist victims. Method. On 19 June 2021, 30 members of the Bikelah community attended a presentation and video screening regarding Basic Life Support. Result: Following an explanation of the Basic Life Support material, the respondents' perception and knowledge of the adoption of BHD increased from 60% to 93%, and their willingness to assist an unconscious victim similarly increased from 53% to 90%. Respondents also had a better understanding of the significance of assisting an unconscious victim prior to the arrival of medical personnel. Conclusion. Because the period of chance to avoid brain cell damage is brief, victims might benefit from basic knowledge and abilities in Basic Life Support. The goal for the future is to deliver mannequin-based training to the broader population.